Changes of DNA methylation and hydroxymethylation in plant protoplast cultures - Moricová, Pavla; Ondřej, Vladan; Navrátilová, Božena; Luhová, Lenka (Acta Biochimica Polonica, 2013)
Cytosine methylation patterns in higher eukaryotes are important in gene regulation. Along with 5-methylcytosine (5-mC), a newly discovered constituent of mammalian DNA, 5-hydroxymethylcytosine (5-hmC), is the other modified base in higher organisms. In this study we detected 5-hmC in plant protoplast DNA and demonstrated its increasing content during the first 72 hrs. of protoplast cultivation. In contrast to 5-hmC, the amount of 5-mC decreased during protoplast cultivation. It was also found that 5-hmC did not primarily arise as a product of oxidative DNA damage following protoplast culture.
Keywords: rostliny; reaktivní formy kyslíku; Plants; Protoplasts; metylace DNA; Cells, Cultured; Cell Survival; viabilita buněk; Reactive Oxygen Species; protoplasty; DNA Methylation; kultivované buňky